ASEAN geology bibliometric analysis: a way forward for sustainable development - Wai, Khoong Tai; Musta, Baba; Kusuma, Kumara Adji; Fei, Chong Kok; Waei, Ow Mun; Teng, Phuah Kit (Geological Society of Malaysia, 2024)
Geology has facilitated societal growth and development. This study analysed the latest development in geology research within 10 ASEAN countries. The VOSviewer software was utilised to examine the distribution of bibliometric maps. The data was acquired from the Scopus database through a data filtering process using the “geology” terms contained in the title, keyword, and abstract. A total of 2,319 articles published between 2018 and 2022 were chosen to capture the prevailing latest circumstances. The findings showed a notable change in geology study throughout the five-year duration, with the number of articles published decreasing from 407 in 2018 to 265 in 2022. The VOSviewer association strength method further revealed the five terms with the highest frequency occurrences, namely geology (794 occurrences), structural geology (259 occurrences), engineering geology (278 occurrences), geophysics (240 occurrences), and remote sensing (214 occurrences). The terms were further categorised into seven distinct clusters, consisting of geology, structural geology, seismology, economic geology, deposits, engineering geology, and volcanoes. Both Indonesia and Malaysia were the most significant countries associated with the geology terms. The emerging latest terms adopted were gas engineering, environmental technology, tourism, machine learning, and sustainable development. This study serves as a valuable point of reference and a source of contemplation for researchers seeking to explore additional research areas, particularly in the field of geology within the ASEAN territory.